Thomas Carlyle: medievalismo e conservadorismo reformista na obra past and present (1843) - Roza, Filipe Lomba Garcia (2019)
This study aims at elucidating the political inclinations and propositions of the scottish historian Thomas Carlyle, with the purpose of discussing his relationship with modern conservative ideology from his work Past and Present (1843). To do so, this work will focus on the debate about medievalism as a defining feature of nineteenth-century romantic writers and on Thomas Carlyle's reform conservatism, highlighting its differences from other phenomena of conservatism in the same century. Despite major emphasis on Past and Present, the work On Heroes (1841) will also be present for discussions about the writing of carlylean History. The analysis of those texts is fundamentally important for defining Thomas Carlyle's place in the great themes – politics, democracy, freedom, and religion – that are still debated contemporarily.